Therapy of leptomeningeal metastasis in solid tumors. (February 2016) - Mack, F.; Baumert, B.G.; Schäfer, N.; Hattingen, E.; Scheffler, B.; Herrlinger, U.; Glas, M.
Highlights: LM diagnosis: highest sensitivity provided by combination of CSF cytology and MRI of whole CNS. Therapeutic spectrum: surgery, radiotherapy, systemic and intrathecal chemotherapy. Treatment depends on type of LM, involvement of CNS parenchyma and systemic situation. Intrathecal chemotherapy is most important in cases of LM of the non-adherent type. Intrathecal therapy: MTX, (liposome-encapsulated) Ara-C, thiotepa are frequently used. Abstract: Leptomeningeal metastasis (LM), i.e. the seeding of tumor cells to the cerebrospinal fluid (CSF) and the leptomeninges, is a devastating and mostly late-stage complication of various solid tumors. Clinical signs and symptoms may include cranial nerve palsies, radicular symptoms, signs of increased intracranial pressure such as headache, nausea and vomiting, and cognitive dysfunction. In cases of suspected LM, the highest diagnostic sensitivity is provided by the combination of CSF cytology and contrast-enhanced MRI (cranial as well as complete spine). The therapeutic spectrum includes radiotherapy of the clinically involved region as well as systemic and intrathecal chemotherapy. The choice of treatment modalities depends on the type of LM (non-adherent tumor cells in the CSF vs. nodular contrast-enhancing tumor growth), additional systemic involvement (uncontrolled vs. controlled systemic disease) and additional involvement of the CNS parenchyma (LM as the only CNS involvement vs. LM + parenchymal CNS metastases). Larger contrast-enhancing nodular LM or symptomatic lesions of the spine may be treated with radiotherapy. In case of uncontrolled systemic disease, the treatment regimen should include systemic chemotherapy. The choice of systemic treatment should take into account the histology of the primary tumor. Intrathecal chemotherapy is most important in cases of LM of the non-adherent type. There are three substances for routine use for intrathecal chemotherapy: methotrexate, cytarabine, and thiotepa. Liposomal cytarabine shows advantages in terms of longer injection intervals, a sufficient distribution in the entire subarachnoid space after lumbar administration and improved quality-of-life. The role of new agents (e.g. rituximab and trastuzumab) for intrathecal therapy is still unclear.